Implication of the Madden-Julian Oscillation in the 40-day variability of the West African Monsoon - (:unkn) unknown (My University, 2009)
Madden-Julian Oscillations (MJO) are extracted over the Indo-Pacific basin using a Local Mode Analysis. The convective perturbations are then projected over a larger domain to evaluate their remote consequences over the West African monsoon (WAM) intraseasonal variability. Rather weak (4 to 6 W m-2) convective fluctuations occurring in-phase with those over the southern Indian basin are found over Africa, confirming the results of Matthews. In reverse, 40-day fluctuations in the WAM, similarly detected and projected over a widened area, demonstrate that a large majority of these events are embedded in the larger-scale patterns of the MJO. The regional amplitude of intraseasonal perturbations of the West African convection is not statistically associated with the amplitude of the MJO over the Indian basin, but is instead closely related to background vertical velocity anomalies over Africa, possibly embedded in changes in the regional Walker-type circulation. Subsiding motion over Africa is recorded during the most energetic convective perturbations in the WAM. Composites analyses over the MJO life cycle, as depicted by the real-time daily indices developed by Wheeler and Hendon, show that positive OLR anomalies during the dry phase are of larger amplitude and spatially more coherent than negative anomalies during the wet phase, especially over the Sahel region. Over West Africa, the phase of suppressed convection is thus of greater importance for the region than the phase of enhanced convection. Rain- gauge records fully confirm these results. The MJO appears significantly involved in the occurrences of dry spells during the monsoon over the Sahel, while large-scale convective clusters are only restricted to the equatorial latitudes and affect thus the Guinean belt, experiencing its short dry season at this time of the year.
Keywords: African Research